Low cerebrospinal fluid concentration of mitochondrial DNA in preclinical Alzheimer disease - Podlesniy, Petar; Figueiro-Silva, Joana; Llado, Albert; Antonell, Anna; Sanchez-Valle, Raquel; Alcolea, Daniel; Lleo, Alberto; Molinuevo, Jose Luis; Serra, Nuria; Trullas, Ramon (Annals of neurology, 2013)
Objective To identify a novel biochemical marker that precedes clinical symptoms in Alzheimer disease (AD). Methods Using quantitative polymerase chain reaction techniques, we measured circulating cell‐free mitochondrial DNA (mtDNA) in cerebrospinal fluid (CSF) from study participants, selected from a cohort of 282 subjects, who were classified according to their concentrations of amyloid β1–42, total tau, and phosphorylated tau and by the presence or absence of dementia, into asymptomatic subjects at risk of AD, symptomatic patients diagnosed with sporadic AD, presymptomatic subjects carrying pathogenic PSEN1 mutations, and patients diagnosed with frontotemporal lobar degeneration (FTLD). We performed equivalent studies in a separate validation cohort of sporadic AD and FTLD patients. In addition, we measured mtDNA copy number in cultured cortical neurons from mutant amyloid precursor protein/presenilin1 (APP/PS1) transgenic mice. Results Asymptomatic patients at risk of AD and symptomatic AD patients, but not FTLD patients, exhibit a significant decrease in circulating cell‐free mtDNA in the CSF. These observations were confirmed in the validation cohort. In addition, presymptomatic subjects carrying pathogenic PSEN1 gene mutations show low mtDNA content in CSF before the appearance of AD‐related biomarkers in CSF. Moreover, mtDNA content in CSF discriminates with high sensitivity and specificity AD patients from either controls or patients with FTLD. Furthermore, cultured cortical neurons from APP/PS1 transgenic mice have fewer mtDNA copies before the appearance of altered synaptic markers. Interpretation Low content of mtDNA in CSF may be a novel biomarker for the early detection of preclinical AD. These findings support the hypothesis that mtDNA depletion is a characteristic pathophysiological factor of neurodegeneration in AD. Ann Neurol 2013;74:655–668